Association between glycolipids and risk of obstructive sleep apnea: A population-based study - Zheng, Murui; Duan, Xueru; Zhou, Huanning; Sun, Weidi; Sun, Guoqiang; Chen, Jianying; Wu, Xiuyi; Rong, Sijing; Huang, Jun; Zhao, Wengjing; Deng, Hai; Liu, Xudong (Frontiers in Nutrition, 2023)
Background This study aimed to investigate the associations between multiple glycolipid biomarkers and the risk of obstructive sleep apnea (OSA). Methods Participants (10,286) aged from 35 to 74 years old were included in this cross-sectional study from the baseline survey of the Guangzhou Heart Study. OSA was ascertained using both Berlin Questionnaire and STOP-BANG Questionnaire. Fasting blood samples were collected from each participant; fasting blood glucose (FBG) and serum concentrations of high-density lipoprotein cholesterol (HDL-CH), low-density lipoprotein cholesterol (LDL-CH), total cholesterol (TC), and triglyceride (TG) were determined. Odds ratio (OR) with 95% confidence interval (CI) was calculated using the multivariate logistic regression model after adjustment for covariates. Results Of the participants included, 15.56% were categorized into the pre-OSA group, and 8.22% into the OSA group. When comparing the highest with the lowest quartiles, HDL-HC was associated with a 22% (OR: 0.78, 95% CI: 0.65–0.94) and 41% (OR: 0.59, 95% CI: 0.45–0.78) reduced risk of pre-OSA and OSA, triglyceride was associated with a 32% (OR 1.32, 95% CI 1.08–1.60) and a 56% (OR 1.56, 95% CI 1.18–2.07) increased risk of pre-OSA and OSA, and FBG was associated with a 1.37-fold (95% CI 1.13–1.67) risk of pre-OSA and 1.38-fold (95% CI 1.03–1.85) risk of OSA. A significant exposure-response trend was observed for HDL-HC, TG, and FBG with both OSA and Pre-OSA (all p < 0.05). No significant association of LDL-CH and TC with the risk of both pre-OSA and OSA was observed. Conclusion The findings suggest that serum HDL-CH was inversely associated with OSA risk, while elevated serum TG and FBG could increase the risk of OSA. Healthy glycolipid metabolism warrants more attention in the field of OSA prevention.